Blueberry can be a future super fruit - Negi, N. D. (Indian Farming, 2019)
In India commercial production of Blueberries is not reported until now but it can be grown in areas having acidic soils with winters cool enough to meet out chilling requirements. Few plants were introduced in Department of Horticulture, CSKHP Krishi Vishwavidyalaya, that showed adaptive to this climate. Generally, Blueberry is a deciduous bush that grows up to 6 to 12 feet (1.8 to 3.6 m) height with fibrous roots which lacks roots hairs. The roots showed mycorrhizal association and continuous supply of inorganic fertilizer that reduced the mycorrhizal population. The commercial production of bush starts after 6 years and flowering takes place is early spring. However, fruits ripen in April-May depending upon varieties and climatic conditions prevailing in that region. Fruits contain various vitamins, antioxidants, minerals and fibre. The calorific value of this berry is very low i.e. 100 g of fresh fruit can provide just 57 calories. Among fruits Blueberries are highest supplier of antioxidants, mainly obtained from anthocyanin compound (chlorogenic acid, tannins, myricetin, quercetin and kaempferol) and other flavonoid such as ï¡- carotene, lutein and zea-xanthin etc. The oxygen radical absorbing capacity of this berry is also very high, which helps to get rid of of harmful free radicals from the body and thus protects the body against aging, cancers and various degenerative diseases.